2020
DOI: 10.1515/epoly-2020-0033
|View full text |Cite
|
Sign up to set email alerts
|

Design and preparation of 3D printing intelligent poly N,N-dimethylacrylamide hydrogel actuators

Abstract: AbstractThe intelligent poly N,N-dimethylacrylamide hydrogel material system with high mechanical strength and the 3D printable property was prepared via in situ free radical polymerization under vacuum successfully. With the increase in nanofibrillated cellulose (NFC) content, stress and strain of hydrogels increased gradually. As the effective reinforcement, NFC enhanced the crosslinking density,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Accordingly, the Boc NEA block consisted of ∼17% of the synthesized polymer, effectively matching the target of 16.67% established by the monomer feed ratio. DMAA was selected as the majority component due to the excellent solubility of polyDMAA in water and the high mechanical strength of the polymer arising from the self-hydrogen bonding capacity DMAA side chains. Mechanical properties were an important consideration when designing microneedles to be prepared using dynamic-covalent crosslinking so as to ensure these had the requisite rigidity and strength to penetrate the dermal layer. The introduction of Boc NEA provides a protected amine side chain on the polymer for subsequent post-synthetic modification, thereby dictating the crosslink density of the resulting network.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the Boc NEA block consisted of ∼17% of the synthesized polymer, effectively matching the target of 16.67% established by the monomer feed ratio. DMAA was selected as the majority component due to the excellent solubility of polyDMAA in water and the high mechanical strength of the polymer arising from the self-hydrogen bonding capacity DMAA side chains. Mechanical properties were an important consideration when designing microneedles to be prepared using dynamic-covalent crosslinking so as to ensure these had the requisite rigidity and strength to penetrate the dermal layer. The introduction of Boc NEA provides a protected amine side chain on the polymer for subsequent post-synthetic modification, thereby dictating the crosslink density of the resulting network.…”
Section: Resultsmentioning
confidence: 99%
“…The authors [ 192 ] took the crossover point as the moment of sol–gel transition at the lowest frequency used, where G ′ and G ″ were proportional to ω 2 and ω, respectively, although the experimental data showing the dependence of this moment on the frequency were also presented. This is a quite common technique for determining gel time at various temperatures [ 66 , 192 , 193 , 194 , 195 ], although (as stated above) this method does not correspond to the real transition and should be considered conditional for usage in technological applications.…”
Section: Sol–gel Transitionmentioning
confidence: 99%
“…15 According to Zhou et al, adding nano-fibrilated cellulose (NFC) to N,N-dimethylacrylamide-based hydrogels increased compressive failure strain by 26% and failure stress by 47%. 16 Likewise, Wang et al reported a drastic improvement in the mechanical properties of VO-based nanocrystalline cellulose (NCC) composites, with up to 700% and 1500% increases in tensile strength and modulus, respectively, but the authors used relatively high NCC loadings (up to 50 wt %). 17 Vidakis et al incorporated 0.5−2.0 wt % NFC into medical grade resin, and after vat photopolymerization, a high-mechanical performance print showed a 114% increase in tensile strength and a 150% increase in tensile modulus with diminished strain value.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Due to its excellent mechanical properties and natural prevalence, nanocellulose represents an attractive option . According to Zhou et al, adding nanofibrilated cellulose (NFC) to N , N -dimethylacrylamide-based hydrogels increased compressive failure strain by 26% and failure stress by 47% . Likewise, Wang et al reported a drastic improvement in the mechanical properties of VO-based nanocrystalline cellulose (NCC) composites, with up to 700% and 1500% increases in tensile strength and modulus, respectively, but the authors used relatively high NCC loadings (up to 50 wt %) .…”
Section: Introductionmentioning
confidence: 99%